An Optimized Ka-Band Low Profile Dual-Polarized Transmitarray Antenna With 2D Beam Switching - Tuloti, Seyed Hashem Ramazannia; Lamecki, Adam; Mrozowski, Michal (IEEE access, 2024)
This article presents an optimized dual-polarized transmitarray antenna (TA) designed for MIMO applications at the Ka-band, capable of switching beams in two directions. The antenna aperture uses a small unit cell with three layers of Taconic RF-35 dielectric substrates, which can be easily fabricated using PCB technology. The unit cell achieved a 360-degree phase shift and a transmission magnitude exceeding–0.4 dB at 28 GHz. We used nine dual-polarized patch antennas in a cross shape, each with a 10.5 dBi gain at 28 GHz, to switch the beams in two directions without changing the feed location. We optimized the phase distribution in the TA aperture and adjusted the feed antenna’s [Formula Omitted] and tilt to achieve a high-gain antenna with low-gain roll-off during beam switching. The fabricated TA exhibited excellent agreement with the full-wave simulation results. It achieved ±15 degrees and ±30 degrees beam tilts in the x- and y- directions, with less than 0.8 dB gain roll-off for both polarizations.